2017
DOI: 10.1038/s41598-017-02159-4
|View full text |Cite
|
Sign up to set email alerts
|

Role of S-Palmitoylation by ZDHHC13 in Mitochondrial function and Metabolism in Liver

Abstract: Palmitoyltransferase (PAT) catalyses protein S-palmitoylation which adds 16-carbon palmitate to specific cysteines and contributes to various biological functions. We previously reported that in mice, deficiency of Zdhhc13, a member of the PAT family, causes severe phenotypes including amyloidosis, alopecia, and osteoporosis. Here, we show that Zdhhc13 deficiency results in abnormal liver function, lipid abnormalities, and hypermetabolism. To elucidate the molecular mechanisms underlying these disease phenotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 49 publications
1
71
0
1
Order By: Relevance
“…In agreement with a recent study 12 conducted in liver of 6-w old Zdhhc13-deficient mice, Zdhhc13 loss-of-function leads to loss of palmitoylation of cytosolic and mitochondrial proteins in brain. While a database search of mitochondrial palmitoylated proteins resulted in >190 proteins in humans and mouse (~26 in rat) with an overlap of 121 (including Drp1; Dataset S1 ), the results presented in this study (i.e., direct protein-protein interaction between Zdhhc13 and Drp1 both in vivo and in vitro ; decreased S -palmitoylation and mitochondrial co-localization in either luc mice or with pharmacological inhibition of S -palmitoylation activity; increased deficits in mitochondrial morphology, distribution and activity) are consistent with Drp1 as one of the substrates of Zdhhc13, and that S -palmitoylation of Drp1 (alone or in concert) affects its translocation to mitochondria likely contributing to the disrupted distribution and lower OXPHOS observed in vivo .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with a recent study 12 conducted in liver of 6-w old Zdhhc13-deficient mice, Zdhhc13 loss-of-function leads to loss of palmitoylation of cytosolic and mitochondrial proteins in brain. While a database search of mitochondrial palmitoylated proteins resulted in >190 proteins in humans and mouse (~26 in rat) with an overlap of 121 (including Drp1; Dataset S1 ), the results presented in this study (i.e., direct protein-protein interaction between Zdhhc13 and Drp1 both in vivo and in vitro ; decreased S -palmitoylation and mitochondrial co-localization in either luc mice or with pharmacological inhibition of S -palmitoylation activity; increased deficits in mitochondrial morphology, distribution and activity) are consistent with Drp1 as one of the substrates of Zdhhc13, and that S -palmitoylation of Drp1 (alone or in concert) affects its translocation to mitochondria likely contributing to the disrupted distribution and lower OXPHOS observed in vivo .…”
Section: Discussionsupporting
confidence: 92%
“…Given that (i) several mitochondrial proteins with clear roles in intermediary metabolism have been shown to be S -palmitoylated in a variety of biological systems 10 12 and (ii) alopecia—as observed in our 3 and another 12 mouse model of Zdhhc13 deficiency—has been linked to mitochondrial dysfunction 13 , 14 , we hypothesized that Zdhhc13 loss-of-function would result in deficits in bioenergetics, not necessarily limited to skin, but to other highly aerobic organs such as brain resulting in behavioral deficits associated with energy distress and altered metabolism of neurotransmitters. While several studies have reported complete S -palmitoylomes, very few have identified specific PAT substrates, the effect of this post-translational modification on the target’s function and the impact of this change at the whole organism level (behavior).…”
Section: Introductionmentioning
confidence: 99%
“…In synaptic spines, these two enzymes were found in vesicles and at the plasma membrane, where they regulate the localization and assembly of synaptic proteins into domains (Fukata et al 2016). Finally, zDHHC8 and zDHHC13 were shown to regulate mitochondria architecture and function (Maynard et al 2008;Shen et al 2017), but mitochondrial localization was not established. Also, these DHHC PATs were found to have roles in other subcellular compartments (Fern andez-Hernando et al 2006;Huang et al 2009;Singaraja et al 2009;Lemonidis et al 2014).…”
Section: Dhhc Protein S-acyltransferasesmentioning
confidence: 99%
“…zDHHC13 has also been linked to metabolism and mitochondrial function. In one study, zDHHC13-deficient mice were found to exhibit hypermetabolism and defective lipid metabolism (Shen et al 2017). Another study focused on the zDHHC13-dependent S-acylation of dynamin-related protein 1 (Drp1) and reported that loss of zDHHC13 in cortex and cerebellum resulted in altered mitochondrial dynamics accompanied by increased glycolysis, glutaminolysis, and lactic acidosis (Napoli et al 2017).…”
Section: Metabolismmentioning
confidence: 99%
“…This may speak to a specificity for LAT palmitoylation by DHHC18 and not DHHC20. As DHHC20 is located at the PM and turnover of LAT palmitoylation is not expected to be rapid, the specificity of Golgi-localized DHHC18 could perhaps reflect a biological reality; this should be confirmed in a cellular context, perhaps with PAT-specific knockouts and subsequent palmitome enrichment, as was recently performed for DHHC13 45,48 .…”
Section: Examining Dhhc18 and Dhhc20 Activity By Oppamentioning
confidence: 76%